2010
DOI: 10.1007/s00253-010-2888-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between bioleaching performance, bacterial community structure and mineralogy in the bioleaching of a copper concentrate in stirred-tank reactors

Abstract: Hugues. Relationship between bioleaching performance, bacterial community structure and mineralogy in the bioleaching of a copper concentrate in stirred-tank reactors. Applied Microbiology and Biotechnology, Springer Verlag, 2011, 89 (2) The experiments undertaken to produce the techno-economic data were also an opportunity to carry out more fundamental research. The objective of this work was to combine the results of the bioleaching experiments, in terms of copper recovery, with the results of bacterial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 39 publications
3
23
0
Order By: Relevance
“…It is reported that the smaller proportion of Sulfobacillus in leaching consortia under continuous conditions was correlated with the reduction of chalcopyrite leaching kinetics than in batch mode. Spolaore et al [11] compared chalcopyrite leaching efficiency of an undefined leaching consortia under continuous condition with that in batch mode. The results show that the leaching kinetics in the continuous test were lower than in the batch test, which can be attributed to a smaller proportion of Sulfobacillus, in agreement with Foucher et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the smaller proportion of Sulfobacillus in leaching consortia under continuous conditions was correlated with the reduction of chalcopyrite leaching kinetics than in batch mode. Spolaore et al [11] compared chalcopyrite leaching efficiency of an undefined leaching consortia under continuous condition with that in batch mode. The results show that the leaching kinetics in the continuous test were lower than in the batch test, which can be attributed to a smaller proportion of Sulfobacillus, in agreement with Foucher et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies (Coram and Rawlings, 2002;Spolaore et al, 2011) showed that Leptospirillum spp. was a major microorganism in a commercial stirred tank reactor at 35-50°C; these results agree with this work.…”
Section: Effects Of the Co 2 Concentration On Bacterial Growth Micromentioning
confidence: 99%
“…Design is further complicated by the multiphase nature of the pulp, consisting of an aqueous solution with cells adhering to the mineral in suspension, and also a suspended solid and air bubbles [7,16].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, parameters such as volumetric productivity and degree of extraction can be significantly increased [7][8][9][10]. Stirred tank reactors (STRs) are also favorable mass transfer devices providing a large gas-liquid interfacial area and high shear stress to enhance the mass transfer [11].…”
Section: Introductionmentioning
confidence: 99%